2002
DOI: 10.1242/jcs.115.10.2099
|View full text |Cite
|
Sign up to set email alerts
|

Embryonal subregion-derived stromal cell lines from novel temperature-sensitive SV40 T antigen transgenic mice support hematopoiesis

Abstract: Throughout life, the hematopoietic system requires a supportive microenvironment that allows for the maintenance and differentiation of hematopoietic stem cells (HSC). To understand the cellular interactions and molecules that provide these functions, investigators have previously established stromal cell lines from the late gestational stage and adult murine hematopoietic microenvironments. However, the stromal cell microenvironment that supports the emergence, expansion and maintenance of HSCs during mid-ges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Signals from the microenvironment are required for HSPC generation. In vitro studies have shown that stromal cell lines derived from E11 AGMs support hematopoiesis in co-cultures with BM HSPCs (Oostendorp et al, 2002a(Oostendorp et al, , 2002b. This was further confirmed in vivo in 2013, when Richard et al (2013) demonstrated that the interaction between the subaortic mesenchyme and the endothelium in the chick embryo was necessary to induce Runx1 expression, a transcription factor required for HSPC generation (Chen et al, 2009).…”
Section: Introductionmentioning
confidence: 86%
“…Signals from the microenvironment are required for HSPC generation. In vitro studies have shown that stromal cell lines derived from E11 AGMs support hematopoiesis in co-cultures with BM HSPCs (Oostendorp et al, 2002a(Oostendorp et al, , 2002b. This was further confirmed in vivo in 2013, when Richard et al (2013) demonstrated that the interaction between the subaortic mesenchyme and the endothelium in the chick embryo was necessary to induce Runx1 expression, a transcription factor required for HSPC generation (Chen et al, 2009).…”
Section: Introductionmentioning
confidence: 86%
“…MOLM-13 cells were seeded at a density of 1×10 6 cells/ml in RPMI medium (Gibco, Life Technologies) with 10% FBS (Gibco, Life Technologies) and 20 U/ml P/S. The murine embryonic stromal cell line EL08-1D2 ( 39 , 40 ) was cultured on gelatin-coated flasks in alphaMEM medium [Gibco, MEM Alpha Medium (1×) + Glutamax I] containing 15% FBS, 5% horse serum, 20 U/ml P/S, and 10 µM 2-mercaptoethanol. Seeding density was 1,000 cells/cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…This layer consists morphologically of a densely packed, round cell layer in the mesenchyme that does not express hematopoietic or endothelial markers, but it does express extracellular matrix proteins suggestive of stroma. In addition, there have been a number of studies in which stromal cell lines have been produced by culturing AGM cells using isolation and culture techniques (i.e., plastic adherence and growth in 10-20% serum containing media) similar to those used for adult MSC [26][27][28]. These stromal cell lines have been primarily characterized on the basis of their ability to support embryonic or adult hematopoiesis and have undergone little phenotypic characterization or analysis of potentiality.…”
Section: What Is the Developmental Origin Of Mscs?mentioning
confidence: 99%